Relevancy and Sustainability of Ayurveda Education and Alternative Medicine in Nepal - Bhusal, Nirmal; Sapkota, Suprich; Upadhyay, Vasudev; Thakur, Siddhartha; Panthi , Sarad (Curriculum Development Journal, 2024)
The study focuses on the preventive aspect of health care and aims to promote healthy lifestyles in school children and tries to prevent and manage the incidence and prevalence of diseases. This research study was done to evaluate the relevancy and sustainability of the program. This study took data from schools of 7 districts, one from each province in Nepal with SAHYP between March to July 2019. Students felt the SAHYP is necessary for them as it makes them aware of medicinal plants, helps them to learn Yoga skills, and remain healthy. The program and its activities are very relevant in context to Nepal as the student needs to learn about the medicinal plants and students have also felt the need of such programs which help them to be healthy and develop healthy habits. The SAHYP should be conducted more frequently with provision of Ayurveda, Yoga teacher and educational materials. Program activities and changes have possibility of being sustainable. Major challenges for sustainability identified include insufficient funds, inadequate physical infrastructures, and lack of trained human resources. Community and institutional ownership and coordination with the local government are required for the sustainability of the programme.